The Role of the Class Teacher in the Development of Character Value in the National Education Perspective - Kiki Melyani Putri; Dwi Dasalinda (research, training and philanthropy institution Natural Aceh, 2023)
The homeroom teacher is the main figure whose role is necessary for students to develop character. This is what encourages researchers to examine what kind of role homeroom teachers need to play in developing the character of their students. The research focuses on describing the role of homeroom teachers, from planning and guiding to instilling the values ​​written in national education. The study in this research is to use a qualitative descriptive model. This research was carried out at SMPIT ARRAHMAH, with the research subjects being homeroom teachers, principals, and several student representatives in each class. After researching data analysis, it was found that the role of homeroom teachers in developing student character at SMPIT ARRAHMAH is to collect information related to students, conduct research on student development and progress, supervise students' daily activities, organize orientation activities, provide direction and motivation to students, organize and place students and monitor social interactions with other individuals, in implementing student character values ​​by national education, namely religious values, honesty, politeness, discipline, independence, and responsibility. Then there are several problems homeroom teachers face in developing the character of SMPIT ARRAHMAH students, which come from the student themes themselves or the student environment.